توزيع الساقط الغباري في مدينة الموصل وماحولها / العراق - سعد الله شهاب عبد المحسن; نزار فضل مازن; جمعة عمر خضر (Latakia University Journal -Engineering Sciences Series, 2019)
The research aimed to indicate the levels of dustfall in different areas of Mosul city, residential, commercial and industrial in addition to a selected sites of small cities in the around sub-boarder in Al-Hatra, Talkif, Sinjar, Al-Qayara, Al-Hamdania and Makhmoor. Dustfall samples were collected from the sites at a height of 4-6 m using dry polyethylene cylindrical containers for the period from December 2007 to October 2008. The collectors were exposed to the atmosphere for a sampling period of 30 days. The results of statistical analysis showed significant difference in the dustfall quantities among the studied sites in the sub-boarder and Mosul city. On the other hand, little difference was observed among different areas of Mosul city. The maximum monthly dustfall was recorded in Al-Hatra city with 185 gm/m2.month. Additionally, the highest frequency of maximum dustfall was occurred in Al-Hatra city with 33.33%, while the highest frequency for the minimum dustfall was recorded in each of Talkif and Sinjar cities with 44.44%. The mean dustfall quantity in Mosul residential area was 16.23 gm/m2.month. The study also found that the dustfall in Mosul city was above the lowest grade of the standard of dustfall. Additionally, the peak dustfall moved between March and September and mostly in March where the storms increased. The results of this research indicate the need to vegetate most of the unplanted areas and to make a green belts around the cities to decrease the dustfall effectively. هدف البحث الحالي إلى تحديد مستويات الساقط الغباري (Dustfall) في مناطق مختلفة من مدينة الموصل شملت السكنية والتجارية والصناعية فضلا عن مناطق مختارة حولها تضمنت الحضر وتلكيف وسنجار والقيارة والحمدانية ومخمور . تم جمع نماذج الساقط الغباري من هذه المواقع لمدة شهر بواسطة جهاز أخذ النماذج المكون من إناء أسطواني مصنوع من مادة البولي اثيلين وضع على ارتفاع 4-6 متر للفترة من كانون الأول 2007 ولغاية تشرين الاول 2008. أظهرت التحليل الإحصائي للنتائج وجود فروقات معنوية في كمية الساقط الغباري بين مدينة الموصل والمناطق الأخرى حولها ، بينما كانت الفروقات قليلة ضمن مدينة الموصل بين المناطق ذات الأنشطة المختلفة . وقد سجلت أعلى كمية للساقط الغباري في مدينة الحضر وبمقدار 185 غم/م2 . شهر ، كما سجل التردد الأعلى لأكبر كمية ساقط غباري في مدينة الحضر أيضاً وبمقدار 33.33% ، بينما سجل التردد الأعلى لأقل كمية ساقط غباري في كل من مدينة تلكيف وسنجار وبمقدار 44.44% . وبلغ معدل الساقط الغباري في المناطق التجارية لمدينة الموصل 16.23 غم/م2 . شهر . كما وجدت الدراسة أن مستوى الساقط الغباري هو أعلى من أدنى مستوى في المحددات . كما تبادل شهرا آذار وأيلول حصول أعلى ساقط غباري وكانت نسبة حصولها في آذار أكثر منها في أيلول نتيجة لازدياد العواصف خلال هذا الشهر . وعلى ضوء هذه النتائج أوصت الدراسة بضرورة التشجير (Vegetation) وزيادة المساحات الخضراء وجعلها بشكل حزام حول المدن المدروسة لتقليل تأثير العواصف وبالتالي الساقط الغباري .